Effect of ph and temperature on the activity of phytase products used in broiler nutrition - Naves,L de P (2012)
The activity of three commercial microbial phytase (Aspergillus oryzae, A. niger, and Saccharomyces cerevisae) products used in broiler nutrition was determined at different pH (2.0 to 9.0) and temperature (20 to 90°C) values. Enzymatic activity was determined according to the reaction of the phytase with its substrate (sodium phytate), in four replicates, and was expressed in units of phytase activity (FTU). A. oryzae phytase exhibited optimal activity at pH 4.0 and 40°C, but its absolute activity was the lowest of the three phytases evaluated. A. niger phytase exhibited maximal activity close to pH 5.0 and 45ºC, whereas S. cerevisae phytase presented its highest activity at pH close to 4.5 and temperatures ranging between 50 and 60°C. It was concluded that A. niger and S. cerevisae phytase products exhibited the highest absolute activities in vitro at pH and temperature values (pH lower than 5.0 and 41ºC) corresponding to the ideal physiological conditions of broilers, which would theoretically allow high hydrolysis rate of the phytate contained in the feed.